Effectiveness of tools and techniques used in sales promotion for hotel industry in Sri Aman / Angella Roger Bujang - Bujang, Angella Roger (2015)
Sales promotion is one f key elements ofpromotional mix which being used by marketers and sales person in order to compete the competitive advantage then increase the sales by stimulating the consumers purchase decision. Since the hotels that exist in Sri Aman, therefore this present ofstudy has made in order to evaluate the effectiveness oftools and techniques used by hotels in Sri Aman. As a self administered questionnaire is prepared and total of 130 respondents are interviewed with it. Then using a SPSS tool program, the collected data is analyzed.